A novel differential filtering SIW power divider with high selectivity. Issue 2 (5th November 2015) - Li, Peng; Chu, Hui; Chen, Rushan S.
ABSTRACT: A novel differential power divider with bandpass filtering response using the substrate integrated waveguide (SIW) technology is presented. An SIW resonant cavity operated in a balanced resonant mode with odd symmetric electric field distribution is utilized to provide both balanced inputs/outputs and expected common‐mode (CM) suppression in a certain band. Meanwhile, by properly constructing the cross‐coupled topology of SIW resonant cavities, the proposed differential power divider achieves a high‐selectivity bandpass filtering response with two transmission zeros on both sides of the passband. The differential power divider is designed and prototyped on a single‐layer printed circuit board (PCB). The measured center frequency is at 10.6 GHz with 490 MHz 3‐dB bandwidth. A good CM suppression can also be achieved within the operating band. The measured in‐band differential‐mode imbalance for magnitude is ±0.3 dB, while for phase is 0°–4°. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:182–188, 2016.